Intercultural sensitivity of teachers in a culturally heterogeneous context in Serbia: Accepting cultural differences or overrating one's intercultural sensitivity? - Dimitrijević Bojana; Petrović Danijela; Zlatković Blagica; Starčević Jelena (Nastava i Vaspitanje)
This paper looks at the intercultural sensitivity of teachers in a culturally heterogeneous context in Serbia, defined in accordance with Milton Bennett's Developmental Model of Intercultural Sensitivity. The main objective of this research was to determine the following: a) the average developmental orientation and perceived orientation scores of the teachers; b) the frequency of participants in different stages of developmental orientation; c) whether there are significant differences between the developmental and the perceived orientation of teachers; d) whether the gap between the perceived and the developmental orientation varies across the developmental continuum in line with the supposition of the Dunning-Kruger effect. The sample consisted of 76 primary school teachers from Vojvodina and South Serbia. Furthermore, the Intercultural Development Inventory (IDI®), used in this research, is based on the theoretical foundations of the selected model of intercultural sensitivity. The results indicate that the mean developmental orientation of teachers is in the range of minimization, while they perceive themselves as more interculturally sensitive, in alignment with the ethno-relativistic orientation of acceptance. The differences between the perceived and the developmental orientations are significant. The gap between the perceived and the developmental orientations decreases with higher intercultural sensitivity, meaning that those teachers who are interculturally sensitive are more objective in assessing their own intercultural sensitivity in comparison with those who are less interculturally sensitive. The implications of the obtained results, when it comes to the professional roles of teachers and their development as reflexive practitioners, are further discussed in this article.